Figural Memory Impairment in Conjunction With Neuropsychiatric Symptoms in IgLON5 Antibody-Associated Autoimmune Encephalitis - Hansen, Niels; Hirschel, Sina; Stöcker, Winfried; Manig, Anja; Falk, Hannah Sönne; Ernst, Marielle; Vukovich, Ruth; Zerr, Inga; Wiltfang, Jens; Bartels, Claudia (Frontiers in Psychiatry, 2020)
Background: IgLON5 disease is an autoimmune disorder that shares neuropathological aspects with a tauopathy. Its clinical spectrum is heterogeneous, and figural memory impairment as an initial phenomenon of IgLON5 syndrome has not yet been described. The rationale of this report is to highlight symptoms related to IgLON5 disease that have not been reported to date. This case report will thereby emphasize how important it is to initiate thorough diagnostic methods including cerebrospinal fluid analysis (CSF) before starting early immunotherapy. Methods: We examined a 65-year-old Caucasian male via neuropsychological tests, magnetic resonance imaging (MRI), electroencephalography (EEG), neurography and polysomnography. He also underwent two lumbar punctures from which we determined specific autoantibodies in cerebrospinal (CSF) and peripheral blood (PB). Results: The patient presented initially complaining of memory loss, gradual dysphagia and sleeping dysfunction. Neuropsychological testing at first presentation and follow-up revealed subtle figural and working memory impairment. At onset and at his 6-month follow-up, we detected IgLON5 antibodies in CSF and PB. Furthermore, we identified in the CSF a blood-brain barrier disturbance at disease onset and follow-up, and markers of neuroaxonal damage such as mildly elevated phosphorylated Tau-181 protein with 86 pg/ml (normal range ≤ 61 pg/ml) at onset. Three months after his initial presentation, he was suffering from axonal neuropathy and transient ataxia in the extremities. Assuming a definitive autoimmune encephalitis-associated with anti-IgLON5 antibodies, we applied high-dose steroids monthly (1g methylprednisolone i.v. for five consecutive days) and his memory complaints, ataxia of extremities and peripheral neuropathy as well as sleeping dysfunction decreased. Conclusions: Our findings broaden IgLON5 disease’s clinical spectrum to include predominant and discrete figural memory impairment together with sleeping dysfunction at disease onset. In addition, our report illustrates how important taking an elaborated diagnostic approach is to assuring an accurate diagnosis and the appropriate therapy if a patient presents with a persisting figural memory impairment and sleeping abnormalities so as to avoid overlooking IgLON5 disease and a potentially poor outcome.